Circulating Dermatan Sulfate and Heparan Sulfate/Heparin Proteoglycans in Children Undergoing Liver Transplantation - Mitchell, Lesley; Superina, Ricardo; Delorme, Michael; Vegh, Patsy; Berry, Leslle; Hoogendoorn, Hugh; Andrew, Maureen (Thrombosis and Haemostasis, 1995)
The liver produces dermatan sulfate (DS), heparan sulfate (HS) and heparin glycosaminoglycans (GAG) and in the presence of hepatic disease, tissue levels of the DS GAG increase dramatically. We hypothesized that in children undergoing liver transplantation plasma levels of DS would be increased. Plasma from children undergoing liver transplantation were tested preoperative, intra operative and post operative at 24-48 h, and 1-3 weeks. Fluctuating levels of DS, HS and heparin anticoagulant activity were detected at all timepoints. The anticoagulant activity was purified and gel chromatography of the material displayed a mean Mr 110,000 D. Reductive elimination decreased the mean Mr 24,000 D indicating the activity resides on a proteoglycan (PG). The purified material was subjected to further chromatography and two peaks of anticoagulant activity resolved, compatible with at least two separate PGs, one with DS GAG chains and the additional PG(s) with HS and heparin GAG chains.